Therapeutic Potential of Endothelial Colony Forming Cells Derived from Human Umbilical Cord Blood - Jia, Jing; Ma, Baitao; Wang, Shaoshuai; Feng, Ling (Current Stem Cell Research & Therapy, 2019)
Endothelial progenitor cells (EPCs) are implicated in multiple biologic processes such as vascular homeostasis, neovascularization and tissue regeneration, and tumor angiogenesis. A subtype of EPCs is referred to as endothelial colony-forming cells (ECFCs), which display robust clonal proliferative potential and can form durable and functional blood vessels in animal models. In this review, we provide a brief overview of EPCs’ characteristics, classification and origins, a summary of the progress in preclinical studies with regard to the therapeutic potential of human umbilical cord blood derived ECFCs (CB-ECFCs) for ischemia repair, tissue engineering and tumor, and highlight the necessity to select high proliferative CB-ECFCs and to optimize their recovery and expansion conditions.
Keywords: Endothelial colony forming cells (ECFCs)